Some Separation Axioms on ωδ — open set - Aziz, Hard i N.; Darwesh, Halgwrd Mohammed; Jabbar, Adil K. (Sulaimani Journal for Pure and Applied Sciences, 2019)
In this paper we introduce some types of separation axioms and study their basic relations with other types of separation axioms such as ω-T_i and δ-T_i, for i=0,1,2.We show that our separation axioms are coarser than ω-T_i and finer than δ-T_i. We determine several crucial properties including that every locally countable space is ω_δ-T_2. Furthermore, we show that the notions T_2 and ω_δ-T_2 are coincide in anti – locally countable space.
Keywords: ωδ open set; ωδTi,i0,1,2,ωδ regular; ωδ normal space